CONSTITUTION AND CONSTITUTIONAL THEORY (Revista Paradigma, 2019)
This paper aims to show two different ways of making constitutional theory. To fulfill the objective, the article presents, first of all, the main elements and characteristics of the constitutional theory developed in the USA. by authors such as Richard Fallon and Jamal Greene. Then, secondly, the text succinctly presents the constitutional theory developed in Italy by authors such as Paolo Comanducci and Riccardo Guastini. From the similarities and differences between both ways of making constitutional theory the article concludes that it is not possible to transplant the form of developing the American constitutional theory to continental law and that the emphasis on certain shared intuitions in the North American discussion can be useful to complement the predominantly theoretical approaches developed in continental law.